2012
DOI: 10.1179/1743284711y.0000000116
|View full text |Cite
|
Sign up to set email alerts
|

Hot rolling bonded multilayered composite steels and varied tensile deformation behaviour

Abstract: Multilayered metal composites consisting of alternating metals or alloys have been well developed to obtain the superior mechanical properties different from those in any of the constituent materials. The layer integrated steel and metals research project sponsored by Japan government started from 2006 and aimed to fabricate steel sheets with high strength (>1200 MPa) and superior elongation (>20), through the composite design of high strength steels and ductile steel layers. In the present work, two kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 9 publications
0
8
0
3
Order By: Relevance
“…It was proposed that the cracks along the laminated interfaces results in the bending of the laminas and enlarging of the deformation volume, and finally gives the ultrahigh impact toughness. 4. The formation mechanisms of the microlaminated DP steel need to be explored further, which would benefit the fabrication and application of the low cost and high performance steel with high strength and high toughness.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that the cracks along the laminated interfaces results in the bending of the laminas and enlarging of the deformation volume, and finally gives the ultrahigh impact toughness. 4. The formation mechanisms of the microlaminated DP steel need to be explored further, which would benefit the fabrication and application of the low cost and high performance steel with high strength and high toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Roll bonding is a type of welding process in which a stack of similar or dissimilar metals is passed through rollers to promote a good bond between the metallic sheets at the cost of reduction in thickness. Yin et al [2] recognized hot roll bonding as the most effective method to fabricate layered materials.…”
Section: Introductionmentioning
confidence: 99%
“…During the impact testing process, the laminated composites can absorb lots of impact works through forming delamination cracks, and it is expected to be applied in the armor equipment and ballistic system. In 2006, Japan government sponsored a research project named "the layer integrated steel and metals," which aims to fabricate multilayer steel with high strength (>1200 MPa) and superior tensile elongation (>20%) through the composite design of high strength steels and ductile steel layers [36]. In 2008, Inoue et al [37] fabricated multilayered SS420/SS304 steel with high toughness and reported that fracture elongation is gradually increasing with the decrease of layer thickness, which is attributed to the decreasing size of tunnel cracks.…”
Section: Laminated Structurementioning
confidence: 99%